1996
DOI: 10.1046/j.1365-201x.1996.488225000.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle buffering capacity is higher in the superficial vastus than in the soleus of spontaneously running rats

Abstract: Skeletal muscle buffering capacity (beta mtitr) was determined in soleus (type I) and superficial vastus (type II) muscles of 16 Long-Evans rats with differing levels of spontaneous activity and in 11 sedentary control rats. beta mtitr was 24% higher (P < 0.001) in superficial vastus muscle than in soleus muscle (268 +/- 50 vs. 216 +/- 30 mumol H+ g muscle dry wt-1 pH unit-1) (mean +/- SD). There was no relationship between beta mtitr and mean weekly running distance amongst spontaneously running rats, nor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…This value was then normalised to the whole pH unit for final display as millimoles H + per gram dry muscle per unit pH and determined as the subject's bm in vitro . The coefficient of variation for the measurement of bm in vitro using this technique in our laboratory is 5.4% and is comparable to that reported elsewhere (Weston et al 1996).…”
Section: Muscle Buffering Capacity; Titration Methods (Bm In Vitro )supporting
confidence: 79%
“…This value was then normalised to the whole pH unit for final display as millimoles H + per gram dry muscle per unit pH and determined as the subject's bm in vitro . The coefficient of variation for the measurement of bm in vitro using this technique in our laboratory is 5.4% and is comparable to that reported elsewhere (Weston et al 1996).…”
Section: Muscle Buffering Capacity; Titration Methods (Bm In Vitro )supporting
confidence: 79%
“…A fall in pH is known to inhibit skeletal muscle contractility (Donaldson et al 1978;Fabiato and Fabiato 1978;Cooke et al 1988). An alternative explanation for this finding is that those subjects with better time trial performances had a higher percentage of fast-twitch fibres than the somewhat slower cyclists, since m has been correlated with the percentage cross-sectional area occupied by type-II fibres (Mannion et al 1995) and type-II fibres have been shown to have a higher m than type-I fibres (Weston et al 1996). However, we are unable to explain why m was not related to a supramaximal test lasting approximately 1 min (TF 150 ).…”
Section: Discussionmentioning
confidence: 94%
“…Homogenates were titrated from pH 7.1 and 6.5 as this was considered representative of muscle pH from rest to exhaustion during intense exercise. The coefficient of variation for the measurement of m titr using this technique in this laboratory is ± 3.0% (Weston et al 1996) and is comparable to that reported elsewhere (Mannion et al 1993). Results are expressed per full pH unit for final expression as mol H + · g muscle dw -1 · pH -1 .…”
Section: Buffering Capacity ( M)mentioning
confidence: 89%
“…Several groups have found that sprint performances are related to percentage of type II fibres [56][57][58][59] and that percentage of type II fibres correlates with β m in men [44,52,60,61] and in rats. [62] More reliable, longitudinal studies [35,[63][64][65] have shown that sprint training either increased or had no effect on β m in previously untrained individuals (table V), but improved power output. Sprint training was also found to have no influence on two muscle metabolites that contribute to β m ( [66][67][68] and humans.…”
Section: Effects Of High-intensity Sprint Training In Previously Untrmentioning
confidence: 99%